A Method for Estimating Students' Desertion in Educational Institutions Using the Analytic Hierarchy Process. (May 2023) - Silva, Hernán A.; Quezada, Luis E.; Oddershede, A. M.; Palominos, Pedro I.; O'Brien, Christopher
The objective of this paper is the design of a predictive model of students' desertion in Educational Institutions based on the Analytic Hierarchy Process (AHP). The proposed model is based on a weighted sum of individual probabilities of desertion associated with various factors (explanatory variables) by experts in the combined use of the AHP and the Ratings technique for the evaluation of the explanatory variables of the model. This proposal was applied in an Institution of Higher Education in Chile. To evaluate the predictive performance of the method, the results were compared with those obtained using Logistic Regression (RL) and with the actual retention of the students in one year. It was found that the proposed method had a 64.6% level of predictability, whereas the model with logistic regression had a 69.9%. It is concluded that it is possible to predict student desertion with a simple model based on the Analytical Hierarchy Process.